Inhalational delivery of induced pluripotent stem cell secretome improves postpneumonectomy lung structure and function - Dane, D. Merrill (J Appl Physiol (1985), 2020)
Cell-free secretory products (secretome) of human induced pluripotent stem cells (iPSCs) have been shown to attenuate tissue injury and facilitate repair and recovery. To examine whether iPSC secretome facilitates mechanically induced compensatory responses following unilateral pneumonectomy (PNX), litter-matched young adult female hounds underwent right PNX (removing 55%–58% of lung units), followed by inhalational delivery of either the nebulized-conditioned media containing induced pluripotent stem cell secretome (iPSC CM) or control cell-free media (CFM); inhalation was repeated every 5 days for 10 treatments. Lung function was measured under anesthesia pre-PNX and 10 days after the last treatment (8 wk post-PNX); detailed quantitative analysis of lung ultrastructure was performed postmortem. Pre-PNX lung function was similar between groups. Compared with CFM control, treatment with iPSC CM attenuated the post-PNX decline in lung diffusing capacity for carbon monoxide and membrane diffusing capacity, accompanied by a 24% larger postmortem lobar volume and distal air spaces. Alveolar double-capillary profiles were 39% more prevalent consistent with enhanced intussusceptive angiogenesis. Frequency distribution of the harmonic mean thickness of alveolar blood-gas barrier shifted toward the lowest values, whereas alveolar septal tissue volume and arithmetic septal thickness were similar, indicating septal remodeling and reduced diffusive resistance of the blood-gas barrier. Thus, repetitive inhalational delivery of iPSC secretome enhanced post-PNX alveolar angiogenesis and septal remodeling that are associated with improved gas exchange compensation. Results highlight the plasticity of the remaining lung units following major loss of lung mass that are responsive to broad-based modulation provided by the iPSC secretome. NEW & NOTEWORTHY To examine whether the secreted products of human induced pluripotent stem cells (iPSCs) facilitate innate adaptive responses following loss of lung tissue, adult dogs underwent surgical removal of one lung, then received repeated administration of iPSC secretory products via inhalational delivery compared with control treatment. Inhalation of iPSC secretory products enhanced capillary formation and beneficial structural remodeling in the remaining lung, leading to improved lung function.